Study Habits of Students Attending Full Day School - Junita Gusri Lillah; Asmidir Ilyas (Universitas Negeri Padang, 2020)
Learning habits are methods or techniques of learning that are carried out repeatedly so as to produce learning skills that remain in students and students will get used to doing it without coercion. This research is motivated by the phenomenon of students who have poor study habits. This study aims to describe the learning habits of students attending full day school. This research is a type of descriptive research using quantitative methods. The population in this study were students of class X and XI of SMAN 1 Coastal Domains totaling 573 students and the sample in this study amounted to 239 students selected using proportional random sampling techniques. The instrument used in this study was a questionnaire about student learning habits with a Likert scale model. Data analysis techniques using descriptive statistical techniques. This study describes (1) students' learning habits based on aspects of making schedules and their implementation in the very good and good category (39.7%), (2) student learning habits based on aspects of reading and taking notes are in the very good category (54.0%), (3) students 'learning habits based on repeating aspects of learning materials are in good categories (46%), (4) students' learning habits based on concentration aspects are in quite good category (43,5%), (5) learning habits students based on aspects of doing the assignment are in good category (48.5%).